Construct validation of academic agency components evaluated on a web platform - Castañeda F., Sandra (2017)
Using data from 1361 students we validate the Meta Evaluador Web where: a) the bank of Study and Self-Regulation Strategies used 50 items calibrated for confirmatory factor analysis. The results of their banks (Cognitive Strategies; Person and Self-Regulation Task and Materials) showed higher rates to 0.90 and RMSEA less than 0.07, with Cronbach alpha’s > 0.83. The fit between the theoretical and empirical models validated their constructs; b) the Personal Epistemology bank, used 12 item calibrated and its adjustment index confirms construct validity (0.90, RMSEA = 0.07) and c) Reading Comprehension bank used 18 calibrated items with convergent validity (CFI = 0.96; RMSEA = 0.03), all of them, with an acceptable homogeneity.